Analysis of potential drug interactions in pulmonary tuberculosis patients in the pediatric clinic - Febria Listina; Yuli Peristiowati (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Analysis of Potential Drug Interactions of Pulmonary Tuberculosis Patients at The Children’s Poly of Imanuel Wayhalim Hospital Bandar Lampung. Tuberculosis (TB) is an infectious disease caused by infection with the bacterium Mycobacterium tuberculosis (MTB). Treatment in tuberculosis patients is given Anti-Tuberculosis Drugs (OAT) consisting of isoniazid, rifampicin, pyrazinamide, ethambutol and streptomycin. Purpose: To analysis of potential drug interactions in pulmonary tuberculosis patients in the pediatric clinic. Method: This study is a non- experimental descriptive study (observational). Sampling using purposive sampling method. The data collection was retrospectively taken from the medical records of tuberculosis patients at the children's poly of Imanuel Wayhalim Hospital Bandar Lampung for the period October – December 2025. Results: The results of the study found that the characteristics of TB patients of the highest age were toddlers (0-5 years) as many as 35 patients (83.3%), the highest sex was male as many as 27 cases (64%), potential drug interactions contained in the therapy of TB pediatric patients were pharmacokinetic interactions in the metabolic phase of OAT and OAT as many as 2 cases (50%), pharmaco dynamic interactions of OAT and OAT as many as 2 cases (50%), pharmaco kinetic interactions in the metabolic phase of OAT and other drugs as many as 10 cases (45.5%), pharmacodynamic interactions of OAT and other drugs as many as 12 cases (54.5%). Based on the severity of OAT and OAT drug interactions, Major results were obtained as many as 2 cases (100%) and the severity of OAT drug interactions and other drugs obtained Moderate results as many as 8 cases (57%), Major as many as 6 cases (43%). Conclusion: Based on research, it can be concluded that anti- tuberculosis drugs that inter actalotarer if ampicin with isoniazid and triamcinolone and the most common type of drug interaction is pharmacokinetics in the metabolic phase. The severity of drug interactions that occur is highest in the moderate category.